METHODS OF TEACHING STUDENTS TO THINK CREATIVELY IN ENGLISH CLASSES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This scientific article talks about the methods of teaching students to think creatively and creatively in English classes, the order of their use, sequence and importance. The purpose of writing this article: Today, the main goal of teaching English is to show the child's creative attitude to reading, the effectiveness of using different methods in English reading literacy. Methods and games: "Five lines" (Sinquain), "Make a list of words with the same vowel in both syllables", "Project", "Salad made of fairy tales"...Result: the main goal of using modern methods is to activate the activity of the students in the educational process, to emphasize the achievement of a high level of assimilation of the educational material.